Autoinflation for hearing loss associated with otitis media with effusion. - Perera, R; Haynes, J; Glasziou, P; Heneghan, C (2006)
BACKGROUND: Otitis media with effusion (OME) or 'glue ear' is an accumulation of fluid in the middle ear, in the absence of acute inflammation or infection. It is the commonest cause of acquired hearing loss in childhood and the usual reason for insertion of 'grommets'. Potential treatments include decongestants, mucolytics, steroids, antihistamines and antibiotics. Autoinflation devices have been proposed as a simple mechanical means of improving 'glue ear'. OBJECTIVES: To determine the effects of autoinflation in adults and children with otitis media with effusion. SEARCH STRATEGY: We searched the Cochrane Ear, Nose and Throat Disorders Group Trials Register, CENTRAL (The Cochrane Library Issue 1, 2006), MEDLINE (1951 to 2006), EMBASE (1974 to 2006) and twelve other databases, using the Cochrane Ear, Nose and Throat Disorders Group search strategy. SELECTION CRITERIA: We selected randomised controlled trials that compared any form of autoinflation to no autoinflation in individuals with 'glue ear'. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed studies for inclusion, assessed quality and extracted data from included studies. MAIN RESULTS: Six studies met the inclusion criteria. Improvement occurred for the composite measure of tympanogram or audiometry at less than one month (Relative Risk of Improvement (RRI) 2.47, 95% confidence interval (CI) 0.93 to 6.58) and at more than one month (RRI 2.20, 95% CI 1.71 to 2.82). Subgroup analysis based on the type of intervention showed a significant effect using a Politzer device under one month (RRI 7.07, 95% CI 3.70 to 13.51) and over one month (RRI 2.25, 95% CI 1.67 to 3.04). Pooled estimates showed non-significant change in tympanometry (type C2 and B) at less than one month (RRI 1.65, 95% CI 0.49 to 5.56) and non-significant improvement in tympanometry at greater than one month (RRI 1.89, 95% CI 0.77 to 4.67). Non-significant improvements occurred for discrete pure tone audiometry (RRI 0.80, 95% CI 0.22 to 2.88) and non-discrete audiometry (WMD 6.95 dB, 95% CI 21.03 to 7.13). None of the studies demonstrated a significant difference in the incidence of side effects between interventions. AUTHORS' CONCLUSIONS: All of the studies were small, of limited treatment duration and short follow up. However, because of the low cost and absence of adverse effects it is reasonable to consider autoinflation whilst awaiting natural resolution of otitis media with effusion. Further research should consider the duration of treatment and the long-term impact of autoinflation on developmental outcomes in children.